2012
DOI: 10.1364/oe.20.024864
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies of femtosecond-laser induced melt dynamics

Abstract: This work presents time-resolved images of femtosecond-laser-induced melt dynamics in 60 nm gold films on glass substrates. Melt dynamics induced by laser radiation with focus diameters of 6 μm and 8 μm (FWHM) at constant laser fluence is investigated with a temporal resolution of 10 ns. In both cases, the formation of the microbumps and gold jets takes at least 250 ns. It is shown that the formation process can be compared to jetting behavior induced by cavitation bubbles near a free liquid surface. This is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 35 publications
5
78
1
1
Order By: Relevance
“…At a later instance (B-images), this ejected dome contracted into a jet like feature, with a contracted droplet at the tip. At these fluence levels the ejection process seems to be dominated by the full melting and the resulting stress relaxation of the heated gold layer, similar to what has been reported for femtosecond LIFT of 60 nm gold layers [84]. Figures 7.2 (f) to 7.2 (g) show the ejection process at higher laser fluence levels.…”
Section: Methodssupporting
confidence: 80%
See 4 more Smart Citations
“…At a later instance (B-images), this ejected dome contracted into a jet like feature, with a contracted droplet at the tip. At these fluence levels the ejection process seems to be dominated by the full melting and the resulting stress relaxation of the heated gold layer, similar to what has been reported for femtosecond LIFT of 60 nm gold layers [84]. Figures 7.2 (f) to 7.2 (g) show the ejection process at higher laser fluence levels.…”
Section: Methodssupporting
confidence: 80%
“…Based on the observations made during low fluence nanosecond LIFT, it assumed that a similar mechanism, as proposed by Unger et al [84] can be employed in order to explain the observed ejection mechanism during nanosecond laser-induced forward transfer. A brief description of the stages of this ejection mechanism is illustrated in figure 7.6.…”
Section: Driving Mechanism Of Jet Ejectionmentioning
confidence: 82%
See 3 more Smart Citations